A Runx1-enhancer Element eR1 Identified Lineage Restricted Mammary Luminal Stem Cells. Issue 1 (19th January 2022) - Matsuo, Junichi; Mon, Naing Naing; Douchi, Daisuke; Yamamura, Akihiro; Kulkarni, Madhura; Heng, Dede Liana; Chen, Sabirah; Nuttonmanit, Napat; Li, Ying; Yang, Henry; Lee, May Yin; Tam, Wai Leong; et al.
Abstract: Mammary gland homeostasis is maintained by adult tissue stem-progenitor cells residing within the luminal and basal epithelia. Dysregulation of mammary stem cells is a key mechanism for cancer development. However, stem cell characterization is challenging because reporter models using cell-specific promoters do not fully recapitulate the mammary stem cell populations. We previously found that a 270-basepair Runx1 enhancer element, named eR1, marked stem cells in the blood and stomach. Here, we identified eR1 activity in a rare subpopulation of the ERα-negative luminal epithelium in mouse mammary glands. Lineage-tracing using an eR1-CreERT2 mouse model revealed that eR1+ luminal cells generated the entire luminal lineage and milk-secreting alveoli—eR1 therefore specifically marks lineage-restricted luminal stem cells. eR1-targeted-conditional knockout of Runx1 led to the expansion of luminal epithelial cells, accompanied by elevated ERα expression. Our findings demonstrate a definitive role for Runx1 in the regulation of the eR1-positive luminal stem cell proliferation during mammary homeostasis. Our findings identify a mechanistic link for Runx1 in stem cell proliferation and its dysregulation in breast cancer. Runx1 inactivation is therefore likely to be an early hit in the cell-of-origin of ERα+ luminal type breast cancer. Graphical Abstract: